Cinema in China: A Bibliometric Journey Through Three Decades of Movie Consumption (1997 - 2024) - Xianxian, Chen; Shafii, A.S. Hardy (STIE Malangkucecwara, 2024)
The entertainment industry, particularly movie consumption, plays a crucial role in cultural diffusion and economic growth. However, with the rapid evolution of media platforms and the changing dynamics of consumer behaviour, understanding the trends, drivers, and impacts of movie consumption in China has become paramount. This study employs a bibliometric analysis of 68 publications from the years 1997 to 2024, utilizing VOSviewer to investigate research publication trends in movie consumption within China. We aim to identify dominant journals, prolific researchers, and leading research organizations in the field, highlight the most cited research publications and their societal impacts, and develop thematic research clusters around the prevalent terms associated with movie consumption behaviour. Using the Web of Science database, we extracted data to fulfill these objectives. Our findings reveal a significant uptick in research interest post-2011, correlating with China’s cinema boom and digital transformation in entertainment consumption. The analysis reveals that